Evidence Based Faktor yang Berhubungan Dengan Kualitas Hidup Pasien PPOK Stabil: A Systematic Review - Ulfa Nur Rohmah; Muhammad Amin; Makhfudli Makhfudli (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
; amin.fkua@gmail.com Makhfudli Fakultas Keperawatan, Universitas Airlangga; ievut_rz@yahoo.com (koresponden) ABSTRACT Background: Low quality of life in chronic obstructive pulmonary disease is crucial because leads to a high risk to reduced activity of daily and mortality. Objective: To identify determine factors that influence with health-related quality of life on stable COPD patients. Method: The database was performed article from Science Direct, CINAHL, Scopus dan PubMed is limited to the last 5 years of publication from 2014 to 2019, full-text article in English. The keywords used ”Health-Related Quality of Life”, “AND”, “Stable”, “AND”, “COPD”. Results: Fourteen articles with 8401 participants were included in the review. Most studies were cross sectional design. COPD Assasment Test (CAT) was to assess health-related quality of life in stable COPD. There was symptoms and exacerbation, functional capacity exercise, psychology, sociodemography, biomolecular, comorbidity, and pulmonary function affecting health-related quality of life on stable COPD patients. Conclusion: Factors might affect with poor HRQOL because the condition of COPD itself which then give an effect to whole body. Suggestion: Health worker need to be aware and control of the complexity of factors influence health-related quality of life to impove outcomes for COPD patients. Keywords: health-related quality of life; chronic obstructive pulmonary disease ABSTRAK Latar belakang: Kualitas hidup yang rendah pada pasien Penyakit Paru Obstruktif Kronik (PPOK) menjadi penting karena dapat menyebabkan penurunan aktivitas sehari-hari dan kematian. Tujuan: Untuk mengetahui determinan faktor yang dapat mempengaruhi kualitas hidup pasien PPOK yang stabil Metode: Database yang digunakan dalam penelitian ini adalah Science Direct, CINAHL, Scopus dan PubMed terbatas untuk publikasi 5 tahun terakhir dari 2014 hingga 2019, full text article dengan berbahasa Inggris. Kata kunci yang digunakan adalah “”Health-Related Quality of Life”, “AND”, “Stable”, “AND”, “COPD”. Hasil: Systematic review ini menggunakan 14 artikel dengan 8401 responden. Kuesioner yang digunakan dalam studi adalah COPD Assasment Test (CAT). Tanda gejala dan eksaserbasi, kapasitas latihan fungsional, psikologi, sosiodemografi, biomolekul, komorbiditas dan faal paru mempengaruhi kualitas hidup pasien PPOK stabil. Kesimpulan: Banyak faktor yang mungkin memiliki hubungan dengan kualitas hidup pasien buruk karena kondisi penyakit PPOK itu sendiri yang kemudian berdampak pada seluruh tubuh. Saran: Petugas kesehatan perlu menyadari dan mengontrol kompleksnya dari faktor-faktor yang mempengaruhi kualitas hidup pasien PPOK sehingga menjadi membaik. Kata kunci: kualitas hidup; penyakit paru obstruktif kronik